Blueprints [compact disc,unabridged] : a novel - Delinsky, Barbara (Macmillan, 2015)
A skilled carpenter and a talented architect are the faces of a local television show called 'Gut It' are faced with a challenge to remaking themselves as well as rebuilding their relationship with each other.